Pengaruh Influencer Marketing dan FOMO terhadap Impulsive Buying Produk Skincare pada Mahasiswa Pengguna TikTok Shop - Cansa Ayu Fernanda; Ria Lestari Pangastuti; Katherin Daniar (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The development of TikTok Shop as a social commerce platform has significantly influenced consumer behavior, particularly in the purchase of skincare products. Exposure to influencer-generated content and the emergence of the Fear of Missing Out (FOMO) phenomenon are considered factors that may increase impulsive buying tendencies among university students. This study aims to analyze the influence of influencer marketing and Fear of Missing Out (FOMO) on impulsive buying behavior toward skincare products among TikTok Shop users. This research employed a quantitative approach using a survey method. The population consisted of sixth-semester students of the Faculty of Economics and Business at Universitas Kadiri who had previously purchased skincare products through TikTok Shop. A total of 139 respondents were selected using a saturated sampling technique. Primary data were collected through a Likert-scale questionnaire and analyzed using SPSS through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination (R²) analysis. The results indicate that influencer marketing has a positive and significant effect on impulsive buying behavior. Fear of Missing Out (FOMO) also has a positive and significant effect on impulsive buying behavior. Simultaneously, both variables were found to have a significant influence on impulsive buying of skincare products through TikTok Shop. The findings suggest that influencer-based marketing strategies and the psychological factor of FOMO play an important role in encouraging impulsive purchasing behavior among students. These results may serve as a reference for business practitioners in developing more effective digital marketing strategies through TikTok Shop.